2009
DOI: 10.1111/j.1558-5646.2009.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

EXTENSIVE VARIATION IN NATURAL COMPETENCE INHAEMOPHILUS INFLUENZAE

Abstract: The ability of some bacteria to take up and recombine DNA from the environment is an important evolutionary problem because its function is controversial; although populations may benefit in the long-term from the introduction of new alleles, cells also reap immediate benefits from the contribution of DNA to metabolism. To clarify how selection has acted, we have characterized competence in natural isolates of H. influenzae by measuring DNA uptake and transformation. Most of the 34 strains we tested became com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 68 publications
5
81
0
1
Order By: Relevance
“…While the greater genetic diversity of NTHi has been speculated to result from increased recombination (Meats et al, 2003), these results suggest that absence of capsule is not a sufficient cause, and other factors are important in facilitating transformation (Maughan & Redfield, 2009). …”
Section: Discussionmentioning
confidence: 79%
“…While the greater genetic diversity of NTHi has been speculated to result from increased recombination (Meats et al, 2003), these results suggest that absence of capsule is not a sufficient cause, and other factors are important in facilitating transformation (Maughan & Redfield, 2009). …”
Section: Discussionmentioning
confidence: 79%
“…Timescales of many millions of years are consistent with the persistence of USS at homologous sites in Pasteurellacean genomes (Bakkali et al 2004), and Pasteurellacean uptake sequences predate the divergence of this family's two major clades (Redfield et al 2006) hundreds of millions of years ago. The costs and benefits of sequencebiased uptake are unlikely to have remained constant over such long periods, being affected not only by the slow accumulation of the preferred sequences in the genome but also by more rapid changes in both external factors (sources and amounts of DNA in the environment) and internal factors [changes in uptake specificity, frequency of recombination, potential for genetic benefits (Redfield et al 2006;Maughan and Redfield 2009)]. Thus the levels of uptake bias and uptake sequence abundance seen in modern bacteria need not represent either true stable equilibria or stages on the way to such equilibria, but may instead integrate the effects of varying selection over long evolutionary periods.…”
Section: 10mentioning
confidence: 99%
“…One key knowledge gap is related to the variability of natural competence among strains, as previous studies were based on a few closely related strains belonging to the same subsp., namely, fastidiosa (Kandel et al 2016;Almeida 2011, 2014;Kung et al 2013). Since both genotypic and phenotypic differences have been described in X. fastidiosa strains (Antonova and Hammer 2015;Coletta-Filho et al 2017;Oliver et al 2014Oliver et al , 2015Parker et al 2012;Scally et al 2005), their natural competence abilities could differ, as is the case reported in other naturally competent bacteria (Bossé et al 2009;Coupat et al 2008;Evans and Rozen 2013;Fujise et al 2004;Gromkova et al 1998;Maughan and Redfield 2009;Sikorski et al 2002). Moreover, although IHR has been detected by MLST studies and was hypothesized to lead to plant host shift (Nunney et al 2012;2014a and2014c), there is still no experimental evidence demonstrating the generation of recombinants by mixing two different subspecies.…”
mentioning
confidence: 99%